David Jones : a Christian modernist? : new approaches to his art, poetry and cultural theory - Callison, Jamie, 1985- (Studies in Religion and the Arts, 2017)
David Jones: A Christian Modernist? is a major reassessment of the work of the poet, artist and essayist David Jones (1895-1974) in light of the complex, ambiguous idea of a 'Christian modernism'. His richly experimental and palimpsestic poetry, art and thought drew extensively on Christian tradition and symbolism as a key to the future: rejecting a technocratic and utilitarian modernity in favour of a revitalised culture of sign and sacrament. This volume examines historical influences on Jones's development, his impassioned engagement with the idea of modernity and with modernist literature and art, the theological sources and resonances of his work, and contemporary or late-modern perspectives on his achievement.